Islamic Education and Intention of Sharia Stock Investment in Pandemic COVID-19: The Role of Islamic Motivation As Mediating Variable - Masiyah Kholmi; Tri Wahyu Oktavendi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to examine the mediating role of Islamic Motivation on the relationship between Islamic Education and the Intention of Sharia Stock Investment during the COVID-19 Pandemic.Design/Methodology/Approach: This research using purposive sampling method with 101 observations of students at University of Muhammadiyah Malang. The data was tested using Smart PLS through several tests, such as Outer Model, Inner Model and Hypothesis Testing.Research findings: The results showed that Islamic education had no effect on Intention of Sharia Stock Investment, but had an effect on Islamic motivation. Islamic motivation influences the intention of sharia stock investment. Furthermore, Islamic Motivation is also able to mediate the relationship between Islamic Ecation and Intention of Sharia Stock Investment. Thus the mediation that occurs is full.Theoretical contribution/Originality: This research can be essential information for higher education in the Intention of Sharia Stock Investment, especially in the COVID-19 Pandemic.Research Implication: This research has implications for policies in the field of education, especially universities in generating investors in Islamic stocks by strengthening understanding and developing Islamic education and Islamic stock investment skills for students.